Let's go to the zoo (Manila : WS Pacific Publications, 2018)
"Which animal is number 1 in the zoo? Lion, giraffe or crocodile ... do you know who?"--Cover.
On board pages.
Keywords: Zoo animals -- Juvenile fiction